Pengaruh Pengetahuan Perpajakan, Pelayanan Fiskus, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan Di Desa Kadokan - Putriana, Rista; Suprihati; Samanto, Hadi (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study aims to examine the influence of tax knowledge, tax officer services, and tax sanctions on taxpayer compliance in paying Land and Building Tax (PBB) in Kadokan Village. A quantitative approach was applied using a simple random sampling method. The sample consisted of 95 taxpayers drawn from a total population of 1,720. Primary data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, as well as t-test and F-test with SPSS version 23. The findings reveal that tax knowledge has a significant positive effect on taxpayer compliance, while tax officer services and tax sanctions show no significant effect. The coefficient of determination (Adjusted R²) of 15.4% indicates that most of the variation in taxpayer compliance is explained by factors outside the tested variables. These results highlight the importance of tax education and outreach programs in enhancing taxpayer compliance with local tax obligations.